Antibacterial PVC decorative film and preparation process thereof
Through the three-layer structure of antibacterial PVC decorative film, nano silver and oxides are used as antibacterial agents, combined with ultrasonic treatment and antioxidants, the problems of raw material accumulation and high cost in the production of PVC decorative film are solved, and efficient antibacterial effect is achieved and Environmentally friendly production process.
Patent Information
- Application Number
- CN202411436706.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-15
- Publication Date
- 2024-12-13
AI Technical Summary
The existing PVC decorative films are prone to accumulation of raw materials during production, and rely on a high proportion of organic antibacterial agents and fillers, which increases costs and causes burden on the environment, making it difficult to effectively solve the antibacterial problem through small costs.
The three-layer structure of antibacterial PVC decorative film, including the epidermal layer, intermediate layer and base layer, uses nanosilver antibacterial agent, zinc oxide and titanium dioxide as antibacterial particles, and is prepared by ultrasonic treatment and drying, combining 1076 and 168 anti-oxygen agent to improve thermal stability and antioxidant properties.
Through the use of a small amount of nano silver antibacterial agent, the cost is reduced, and the antibacterial particle size screening and the synergistic effect of antioxidants is achieved, and the antibacterial effect and thermal stability are maintained, and the excellent antibacterial properties are maintained. Improves production flexibility and efficiency.
Smart Images

Figure CN119116498A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of decorative films, in particular to an antibacterial PVC decorative film and a preparation process thereof. Background Art
[0002] With the gradual improvement of people's living standards and the rise of the real estate industry, surface decoration materials have entered a period of rapid development. Among them, film materials such as PVC film, PET film and composite film have occupied a dominant position in the new surface decoration material market due to their simple production process, diverse surface decoration patterns and effects, simple use methods and extremely high cost performance. PVC film has good wear resistance, good corrosion resistance, high quality and low price. It has developed rapidly and is widely used in indoor and furniture decoration, decoration industry, aircraft cabin membrane, cabin membrane and other fields. It can make the surface of the decorated object have a higher hardness, prevent the surface from being scratched, abraded or bumped by humans, so as to better protect the decorated object and increase its service life; secondly, it can also make the decorated object have the characteristics of high temperature resistance to prevent surface burns. In addition, PVC can not only show the colors of nature, but also the colors of people's imagination.
[0003] However, the existing PVC decorative films are all pressed in an integrated manner during production, which easily causes the accumulation of raw materials on the production side. Secondly, with the emphasis on environmental protection and sustainable development, the development of low-toxic and environmentally friendly materials has become an inevitable trend. Many existing antibacterial PVC materials often rely on a higher proportion of organic antibacterial agents and fillers, which not only increases costs, but may also burden the environment. Summary of the invention
[0004] In view of the fact that the existing PVC decorative films are all pressed in an integrated manner during production, this method easily causes the accumulation of raw materials on the production side. Secondly, with the emphasis on environmental protection and sustainable development, the development of low-toxic and environmentally friendly materials has become an inevitable trend. Many existing antibacterial PVC materials often rely on a higher proportion of organic antibacterial agents and fillers, which not only increases the cost, but may also cause a burden on the environment. The present invention is proposed.
[0005] Therefore, the problem to be solved by the present invention is that the antibacterial problem cannot be effectively solved at a low cost.
[0006] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0007] In a first aspect, an embodiment of the present invention provides an antibacterial PVC decorative film, which includes a skin layer, an intermediate layer, and a base layer;
[0008] The epidermis layer comprises the following raw material components in weight ratio: 80-100 parts of PVC resin, 15-25 parts of plasticizer, and 0.05-0.1 parts of nano silver antibacterial agent;
[0009] The middle layer comprises the following raw material components in weight ratio: 45-85 parts of PVC resin, 1-5 parts of heat stabilizer, 5-20 parts of titanium dioxide, 0.1-0.3 parts of 1076 antioxidant, 0.1-0.3 parts of 168 antioxidant, and 2.5-3.75 parts of antibacterial particles;
[0010] The base layer comprises the following raw material components in weight ratio: 100-120 parts of PVC resin, 5-20 parts of inorganic non-metallic nano filler, 1-10 parts of coupling agent, and 20 parts of calcium carbonate powder.
[0011] As a preferred embodiment of the antibacterial PVC decorative film of the present invention, the antibacterial particles include the following raw material components in weight ratio: 1.5-2 parts of nano silver particles, 0.5-0.75 parts of zinc oxide, and 0.5-1 parts of titanium dioxide;
[0012] The preparation method of the nano silver particles comprises:
[0013] Dissolving silver nitrate in deionized water to prepare a silver ion solution, and stirring the silver ion solution;
[0014] Add a reducing agent to the silver ion solution, wait for 15-30 minutes, set the temperature at 20-35°C, and obtain an intermediate;
[0015] Add a stabilizer to the intermediate, stir for 15-30 minutes, and separate by centrifugation or filtration to obtain nanosilver particles;
[0016] The preparation method of the zinc oxide comprises:
[0017] Dissolve zinc chloride in deionized water and set the pH range to ensure precipitation of zinc oxide;
[0018] Add sodium hydroxide solution and stir to form zinc oxide precipitation;
[0019] Finally, the precipitate is separated by centrifugation or filtration, washed and dried to obtain zinc oxide powder;
[0020] Among them, the pH range was set to 7.8-9.2;
[0021] The preparation method of titanium dioxide comprises:
[0022] Dilute tetrabutyl titanate in a ratio of 1-2:10, add it into deionized water, and stir evenly;
[0023] The heating is performed, the temperature is set at 250-320°C, the calcination time is set to 45-75min, and finally cooling is performed to form titanium dioxide particles.
[0024] As a preferred embodiment of the antibacterial PVC decorative film of the present invention, the preparation method of the antibacterial particles comprises:
[0025] Mixing nanosilver particles, zinc oxide, and titanium dioxide, and stirring in deionized water;
[0026] Ultrasonic treatment is performed on the mixed solution using an ultrasonic cleaner, and the treatment time is set to 15-45 minutes to obtain a mixture;
[0027] The ultrasonically treated mixture was transferred to a dryer, the temperature was set at 60-80°C, and the drying time was 3-5 h;
[0028] The dried mixture was pulverized and sieved using a mesh size of 100-130 μm.
[0029] As a preferred embodiment of the antibacterial PVC decorative film of the present invention, the preparation method of the nano silver antibacterial agent comprises:
[0030] Select PVP or PVA and dissolve them in deionized water at a ratio of 1-10% to obtain a polymer solution;
[0031] Add nanosilver particles to deionized water at a ratio of 0.1-0.5%, then add the polymer solution and stir for no less than 30 minutes;
[0032] Then, the mixture is treated in an ultrasonic cleaner for 15-30 minutes to form composite particles;
[0033] The composite particles were then placed in a centrifuge and spun at 8000 rpm for 10-15 min to remove unbound composite particles;
[0034] Add deionized water to the centrifuge tube and wash the obtained precipitate with deionized water;
[0035] Finally, the composite particles are dried at a temperature of 50-60° C. to obtain the nano-silver antibacterial agent.
[0036] As a preferred embodiment of the antibacterial PVC decorative film of the present invention, the inorganic non-metallic nanofiller includes the following raw material components in weight ratio: 3-10 parts of nano silicon dioxide, 2-6 parts of nano zinc oxide, 1-4 parts of nano titanium dioxide, 1-3 parts of nano zirconium oxide, and 5-15 parts of nano calcium carbonate.
[0037] As a preferred embodiment of the antibacterial PVC decorative film of the present invention, the preparation method of the inorganic non-metallic nanofiller comprises:
[0038] Add nano silicon dioxide, nano zinc oxide, nano titanium dioxide, nano zirconium oxide, and nano calcium carbonate into a mixing container in a ratio of 3:2:1:1:5;
[0039] Use a mechanical stirrer for initial mixing, and set the stirring time to 30-45 minutes;
[0040] Add deionized water or ethanol to the mixing container, the added solution is 5-10% of the total amount, and continue to stir with a stirrer for 5-15 minutes;
[0041] Use ultrasonic processing equipment for treatment, set the power to 100-500W, and the treatment time to 5-20min;
[0042] The mixture after ultrasonic treatment is added into a vacuum dryer, the temperature is set to 40-60° C., the vacuum degree is 0.1-0.5 atm, and the drying time is 6-12 h to obtain an inorganic non-metallic nanofiller.
[0043] In a second aspect, an embodiment of the present invention provides a process for preparing an antibacterial PVC decorative film, which comprises the following steps:
[0044] The base layer, the middle layer, and the epidermis layer are prepared simultaneously;
[0045] Laying an intermediate layer on the base layer, bonding the intermediate layer by ultrasonic hot pressing to form a finished part, and cooling the finished part;
[0046] The surface layer is superimposed on the cooled finished part, starch is applied, and then ultrasonic hot pressing is used to bond the part to form a PVC decorative film.
[0047] Input the cutting size and use the automatic cutting machine to complete the cutting of the PVC decorative film.
[0048] As a preferred solution of the preparation process of the antibacterial PVC decorative film of the present invention, in the preparation process of the to-be-finished part, the ultrasonic wave is used for 5-10 seconds and the temperature is set to 70-150°C.
[0049] As a preferred solution of the preparation process of the antibacterial PVC decorative film of the present invention, when forming the PVC decorative film, the ultrasonic wave is used for 2-6 seconds and the temperature is set to 50-120°C.
[0050] As a preferred solution of the preparation process of the antibacterial PVC decorative film of the present invention, after the PVC decorative film is cut, the adhesion of the edge of the PVC decorative film is detected, and a threshold of the adhesion is set. When the detected value exceeds the set threshold, the PVC decorative film is judged to be qualified.
[0051] The beneficial effects of the present invention are as follows: by using a small amount of nano silver antibacterial agent, the cost can be reduced; by screening the particle size of the antibacterial particles used, a higher specific surface area and a stronger antibacterial effect can be obtained, and silver ions can be released more effectively, ensuring that the present invention can still maintain excellent antibacterial properties.
[0052] The combination of 1076 antioxidant and 168 antioxidant will produce a synergistic effect. As the main antioxidant, 1076 antioxidant can capture free radicals and interrupt the oxidation chain reaction, while 168 antioxidant acts as an auxiliary antioxidant to decompose the hydroperoxides produced by the oxidation process to prevent them from further initiating oxidation reactions. Compared with using one antioxidant alone, this combination often provides better thermal stability and antioxidant properties.
[0053] A three-layer setting of a surface layer, a middle layer, and a base layer is adopted, and each layer can be produced separately. When one of the layers is missing, only that layer needs to be produced. Compared with the overall processing method, this method can be more flexible, and the surface layer, the middle layer and the base layer can be prepared in advance, which can shorten the production time when producing PVC decorative film. BRIEF DESCRIPTION OF THE DRAWINGS
[0054] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work. Among them:
[0055] Figure 1 The figure is a flow chart of antibacterial PVC decorative film and its preparation process. DETAILED DESCRIPTION
[0056] In order to make the above-mentioned purposes, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the drawings of the specification. Obviously, the described embodiments are part of the embodiments of the present invention, but not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary persons in the art without creative work should fall within the scope of protection of the present invention.
[0057] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0058] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.
[0059] Example 1
[0060] The first embodiment of the present invention provides an antibacterial PVC decorative film, comprising a skin layer, an intermediate layer, and a base layer;
[0061] The epidermis layer comprises the following raw material components in weight ratio: 80 parts of PVC resin, 15 parts of plasticizer, and 0.05 parts of nano silver antibacterial agent;
[0062] The middle layer includes the following raw material components in weight ratio: 45 parts of PVC resin, 1 part of heat stabilizer, 5 parts of titanium dioxide, 0.1 parts of 1076 antioxidant, 0.1 parts of 168 antioxidant, and 2.5 parts of antibacterial particles;
[0063] The base layer comprises the following raw material components in weight ratio: 100 parts of PVC resin, 5 parts of inorganic non-metallic nano filler, 3 parts of coupling agent, and 20 parts of calcium carbonate powder.
[0064] The antibacterial particles include the following raw material components in weight ratio: 1.5 parts of nano silver particles, 0.5 parts of zinc oxide, and 0.5 parts of titanium dioxide;
[0065] The preparation method of the nano silver particles comprises:
[0066] Dissolving silver nitrate in deionized water to prepare a silver ion solution, and stirring the silver ion solution;
[0067] Add a reducing agent to the silver ion solution, wait for 15-30 minutes, set the temperature at 20-35°C, and obtain an intermediate;
[0068] Add a stabilizer to the intermediate, stir for 15-30 minutes, and separate by centrifugation or filtration to obtain nanosilver particles;
[0069] The preparation method of the zinc oxide comprises:
[0070] Dissolve zinc chloride in deionized water and set the pH range to ensure precipitation of zinc oxide;
[0071] Add sodium hydroxide solution and stir to form zinc oxide precipitation;
[0072] Finally, the precipitate is separated by centrifugation or filtration, washed and dried to obtain zinc oxide powder;
[0073] Among them, the pH range was set to 7.8;
[0074] The preparation method of titanium dioxide comprises:
[0075] Dilute tetrabutyl titanate in a ratio of 1-2:10, add it into deionized water, and stir evenly;
[0076] The heating is performed, the temperature is set at 250-320°C, the calcination time is set to 45-75min, and finally cooling is performed to form titanium dioxide particles.
[0077] The method for preparing the antibacterial particles comprises:
[0078] Mixing nanosilver particles, zinc oxide, and titanium dioxide, and stirring in deionized water;
[0079] Ultrasonic treatment is performed on the mixed solution using an ultrasonic cleaner, and the treatment time is set to 15-45 minutes to obtain a mixture;
[0080] The ultrasonically treated mixture was transferred to a dryer, the temperature was set at 60-80°C, and the drying time was 3-5 h;
[0081] The dried mixture was pulverized and sieved using a 100 μm mesh.
[0082] The preparation method of the nano silver antibacterial agent comprises:
[0083] Select PVP or PVA and dissolve them in deionized water at a ratio of 1-10% to obtain a polymer solution;
[0084] Add nanosilver particles to deionized water at a ratio of 0.1-0.5%, then add the polymer solution and stir for no less than 30 minutes;
[0085] Then, the mixture is treated in an ultrasonic cleaner for 15-30 minutes to form composite particles;
[0086] The composite particles were then placed in a centrifuge and spun at 8000 rpm for 10-15 min to remove unbound composite particles;
[0087] Add deionized water to the centrifuge tube and wash the obtained precipitate with deionized water;
[0088] Finally, the composite particles are dried at a temperature of 50-60° C. to obtain the nano-silver antibacterial agent.
[0089] The inorganic non-metallic nano filler comprises the following raw material components in weight ratio: 3 parts of nano silicon dioxide, 2 parts of nano zinc oxide, 1 part of nano titanium dioxide, 1 part of nano zirconium oxide, and 5 parts of nano calcium carbonate.
[0090] The preparation method of the inorganic non-metallic nanofiller comprises:
[0091] Add nano silicon dioxide, nano zinc oxide, nano titanium dioxide, nano zirconium oxide, and nano calcium carbonate into a mixing container in a ratio of 3:2:1:1:5;
[0092] Use a mechanical stirrer for initial mixing, and set the stirring time to 30-45 minutes;
[0093] Add deionized water or ethanol to the mixing container, the added solution is 5-10% of the total amount, and continue to stir with a stirrer for 5-15 minutes;
[0094] Use ultrasonic processing equipment for treatment, set the power to 100-500W, and the treatment time to 5-20min;
[0095] The mixture after ultrasonic treatment is added into a vacuum dryer, the temperature is set to 40-60° C., the vacuum degree is 0.1-0.5 atm, and the drying time is 6-12 h to obtain an inorganic non-metallic nanofiller.
[0096] Example 2
[0097] The second embodiment of the present invention provides an antibacterial PVC decorative film, comprising a skin layer, an intermediate layer, and a base layer;
[0098] The epidermis layer comprises the following raw material components in weight ratio: 90 parts of PVC resin, 20 parts of plasticizer, and 0.07 parts of nano silver antibacterial agent;
[0099] The middle layer includes the following raw material components in weight ratio: 60 parts of PVC resin, 3 parts of heat stabilizer, 12 parts of titanium dioxide, 0.2 parts of 1076 antioxidant, 0.2 parts of 168 antioxidant, and 3 parts of antibacterial particles;
[0100] The base layer comprises the following raw material components in weight ratio: 110 parts of PVC resin, 12 parts of inorganic non-metallic nano filler, 6 parts of coupling agent, and 20 parts of calcium carbonate powder.
[0101] The antibacterial particles include the following raw material components in weight ratio: 1.75 parts of nano silver particles, 0.5 parts of zinc oxide, and 0.75 parts of titanium dioxide;
[0102] The preparation method of the nano silver particles comprises:
[0103] Dissolving silver nitrate in deionized water to prepare a silver ion solution, and stirring the silver ion solution;
[0104] Add a reducing agent to the silver ion solution, wait for 15-30 minutes, set the temperature at 20-35°C, and obtain an intermediate;
[0105] Add a stabilizer to the intermediate, stir for 15-30 minutes, and separate by centrifugation or filtration to obtain nanosilver particles;
[0106] The preparation method of the zinc oxide comprises:
[0107] Dissolve zinc chloride in deionized water and set the pH range to ensure precipitation of zinc oxide;
[0108] Add sodium hydroxide solution and stir to form zinc oxide precipitation;
[0109] Finally, the precipitate is separated by centrifugation or filtration, washed and dried to obtain zinc oxide powder;
[0110] Among them, the pH range was set to 7.8;
[0111] The preparation method of titanium dioxide comprises:
[0112] Dilute tetrabutyl titanate in a ratio of 1-2:10, add it into deionized water, and stir evenly;
[0113] The heating is performed, the temperature is set at 250-320°C, the calcination time is set to 45-75min, and finally cooling is performed to form titanium dioxide particles.
[0114] The method for preparing the antibacterial particles comprises:
[0115] Mixing nanosilver particles, zinc oxide, and titanium dioxide, and stirring in deionized water;
[0116] Ultrasonic treatment is performed on the mixed solution using an ultrasonic cleaner, and the treatment time is set to 15-45 minutes to obtain a mixture;
[0117] The ultrasonically treated mixture was transferred to a dryer, the temperature was set at 60-80°C, and the drying time was 3-5 h;
[0118] The dried mixture was pulverized and sieved using a 115 μm mesh.
[0119] The preparation method of the nano silver antibacterial agent comprises:
[0120] Select PVP or PVA and dissolve them in deionized water at a ratio of 1-10% to obtain a polymer solution;
[0121] Add nanosilver particles to deionized water at a ratio of 0.1-0.5%, then add the polymer solution and stir for no less than 30 minutes;
[0122] Then, the mixture is treated in an ultrasonic cleaner for 15-30 minutes to form composite particles;
[0123] The composite particles were then placed in a centrifuge and spun at 8000 rpm for 10-15 min to remove unbound composite particles;
[0124] Add deionized water to the centrifuge tube and wash the obtained precipitate with deionized water;
[0125] Finally, the composite particles are dried at a temperature of 50-60° C. to obtain the nano-silver antibacterial agent.
[0126] The inorganic non-metallic nano filler comprises the following raw material components in weight ratio: 6 parts of nano silicon dioxide, 4 parts of nano zinc oxide, 2 parts of nano titanium dioxide, 2 parts of nano zirconium oxide, and 10 parts of nano calcium carbonate.
[0127] The preparation method of the inorganic non-metallic nanofiller comprises:
[0128] Add nano silicon dioxide, nano zinc oxide, nano titanium dioxide, nano zirconium oxide, and nano calcium carbonate into a mixing container in a ratio of 3:2:1:1:5;
[0129] Use a mechanical stirrer for initial mixing, and set the stirring time to 30-45 minutes;
[0130] Add deionized water or ethanol to the mixing container, the added solution is 5-10% of the total amount, and continue to stir with a stirrer for 5-15 minutes;
[0131] Use ultrasonic processing equipment for treatment, set the power to 100-500W, and the treatment time to 5-20min;
[0132] The mixture after ultrasonic treatment is added into a vacuum dryer, the temperature is set to 40-60° C., the vacuum degree is 0.1-0.5 atm, and the drying time is 6-12 h to obtain an inorganic non-metallic nanofiller.
[0133] Example 3
[0134] The third embodiment of the present invention provides an antibacterial PVC decorative film, comprising a skin layer, an intermediate layer, and a base layer;
[0135] The epidermis layer comprises the following raw material components in weight ratio: 100 parts of PVC resin, 25 parts of plasticizer, and 0.1 parts of nano silver antibacterial agent;
[0136] The middle layer includes the following raw material components in weight ratio: 85 parts of PVC resin, 5 parts of heat stabilizer, 20 parts of titanium dioxide, 0.3 parts of 1076 antioxidant, 0.3 parts of 168 antioxidant, and 3.75 parts of antibacterial particles;
[0137] The base layer comprises the following raw material components in weight ratio: 120 parts of PVC resin, 20 parts of inorganic non-metallic nano filler, 10 parts of coupling agent, and 20 parts of calcium carbonate powder.
[0138] The antibacterial particles include the following raw material components in weight ratio: 2 parts of nano silver particles, 0.75 parts of zinc oxide, and 1 part of titanium dioxide;
[0139] The preparation method of the nano silver particles comprises:
[0140] Dissolving silver nitrate in deionized water to prepare a silver ion solution, and stirring the silver ion solution;
[0141] Add a reducing agent to the silver ion solution, wait for 15-30 minutes, set the temperature at 20-35°C, and obtain an intermediate;
[0142] Add a stabilizer to the intermediate, stir for 15-30 minutes, and separate by centrifugation or filtration to obtain nanosilver particles;
[0143] The preparation method of the zinc oxide comprises:
[0144] Dissolve zinc chloride in deionized water and set the pH range to ensure precipitation of zinc oxide;
[0145] Add sodium hydroxide solution and stir to form zinc oxide precipitation;
[0146] Finally, the precipitate is separated by centrifugation or filtration, washed and dried to obtain zinc oxide powder;
[0147] Among them, the pH range was set to 7.8;
[0148] The preparation method of titanium dioxide comprises:
[0149] Dilute tetrabutyl titanate in a ratio of 1-2:10, add it into deionized water, and stir evenly;
[0150] The heating is performed, the temperature is set at 250-320°C, the calcination time is set to 45-75min, and finally cooling is performed to form titanium dioxide particles.
[0151] The method for preparing the antibacterial particles comprises:
[0152] Mixing nanosilver particles, zinc oxide, and titanium dioxide, and stirring in deionized water;
[0153] Ultrasonic treatment is performed on the mixed solution using an ultrasonic cleaner, and the treatment time is set to 15-45 minutes to obtain a mixture;
[0154] The ultrasonically treated mixture was transferred to a dryer, the temperature was set at 60-80°C, and the drying time was 3-5 h;
[0155] The dried mixture was pulverized and sieved using a 130 μm mesh.
[0156] The preparation method of the nano silver antibacterial agent comprises:
[0157] Select PVP or PVA and dissolve them in deionized water at a ratio of 1-10% to obtain a polymer solution;
[0158] Add nanosilver particles to deionized water at a ratio of 0.1-0.5%, then add the polymer solution and stir for no less than 30 minutes;
[0159] Then, the mixture is treated in an ultrasonic cleaner for 15-30 minutes to form composite particles;
[0160] The composite particles were then placed in a centrifuge and spun at 8000 rpm for 10-15 min to remove unbound composite particles;
[0161] Add deionized water to the centrifuge tube and wash the obtained precipitate with deionized water;
[0162] Finally, the composite particles are dried at a temperature of 50-60° C. to obtain the nano-silver antibacterial agent.
[0163] The inorganic non-metallic nano filler comprises the following raw material components in weight ratio: 10 parts of nano silicon dioxide, 6 parts of nano zinc oxide, 4 parts of nano titanium dioxide, 3 parts of nano zirconium oxide, and 15 parts of nano calcium carbonate.
[0164] The preparation method of the inorganic non-metallic nanofiller comprises:
[0165] Add nano silicon dioxide, nano zinc oxide, nano titanium dioxide, nano zirconium oxide, and nano calcium carbonate into a mixing container in a ratio of 3:2:1:1:5;
[0166] Use a mechanical stirrer for initial mixing, and set the stirring time to 30-45 minutes;
[0167] Add deionized water or ethanol to the mixing container, the added solution is 5-10% of the total amount, and continue to stir with a stirrer for 5-15 minutes;
[0168] Use ultrasonic processing equipment for treatment, set the power to 100-500W, and the treatment time to 5-20min;
[0169] The mixture after ultrasonic treatment is added into a vacuum dryer, the temperature is set to 40-60° C., the vacuum degree is 0.1-0.5 atm, and the drying time is 6-12 h to obtain an inorganic non-metallic nanofiller.
[0170] Comparative Example 1: Compared with Examples 1 to 3, the same ingredients are used, but the layers are not arranged, but the layers are formed in an integrated manner.
[0171] Comparative Example 2: Compared with Examples 1 to 3, the difference is that no antibacterial particles are used.
[0172] Comparative Example 3: Compared with Examples 1 to 3, only one of the 1076 antioxidant and the 168 antioxidant is used.
[0173] Comparative Example 4: Compared with Examples 1 to 3, the difference is that no inorganic non-metallic nanofiller is used.
[0174] The performance test table of the PVC decorative films obtained in Examples 1 to 3 and Comparative Examples 1 to 4 is shown in Table 1:
[0175] Table 1: Performance comparison of PVC decorative films made under different formulations:
[0176]
[0177] Experimental data description:
[0178] Antibacterial properties: The antibacterial effects of samples on common bacteria (such as Escherichia coli and Staphylococcus aureus) were determined by the plate count method.
[0179] Antioxidant property: Oxidation test is carried out using oxidants (such as hydrogen peroxide) to determine the antioxidant effect of the sample.
[0180] Aging resistance: The durability of the samples was evaluated through accelerated aging experiments (such as UV light irradiation).
[0181] Mechanical strength: The tensile strength of the samples was determined by tensile testing.
[0182] Flexibility: The maximum elongation of the sample is measured by tensile test.
[0183] Thermal stability: The thermal decomposition temperature of the material was determined by thermogravimetric analysis (TGA).
[0184] The performance comparison of Examples 1 to 3 is shown in Table 2:
[0185] Table 2: Performance comparison table of Example 1 to Example 3:
[0186]
[0187]
[0188] It can be seen from Table 2 that the increase of ingredients will increase the overall antibacterial properties, thermal stability, and antioxidant properties, but shorten the flexibility.
[0189] Example 4
[0190] The fourth embodiment of the present invention provides a process for preparing an antibacterial PVC decorative film, comprising the following steps:
[0191] S1. Synchronously prepare the base layer, middle layer, and epidermis layer.
[0192] S2, stacking an intermediate layer on the base layer, and then bonding by ultrasonic hot pressing to form a finished part, and cooling the finished part.
[0193] During the preparation of the to-be-finished part, the ultrasonic wave is used for 5-10 seconds and the temperature is set at 70-150°C.
[0194] S3. Overlay a skin layer on the cooled finished workpiece, apply starch, and then bond by ultrasonic hot pressing to form a PVC decorative film.
[0195] When forming the PVC decorative film, the ultrasonic wave is used for 2-6 seconds and the temperature is set to 50-120°C.
[0196] S4. Input cutting size and use automatic cutting machine to complete cutting of PVC decorative film.
[0197] After the PVC decorative film is cut, the adhesion of the edge of the PVC decorative film is tested, and a threshold of the adhesion is set. When the detected value exceeds the set threshold, the PVC decorative film is judged to be qualified.
[0198] In summary, the method can reduce the cost by using a small amount of nano-silver antibacterial agent, and has a higher specific surface area and a stronger antibacterial effect by screening the particle size of the antibacterial particles used, and can release silver ions more effectively, ensuring that the present invention can still maintain excellent antibacterial properties.
[0199] The combination of 1076 antioxidant and 168 antioxidant will produce a synergistic effect. As the main antioxidant, 1076 antioxidant can capture free radicals and interrupt the oxidation chain reaction, while 168 antioxidant acts as an auxiliary antioxidant to decompose the hydroperoxides produced by the oxidation process to prevent them from further initiating oxidation reactions. Compared with using one antioxidant alone, this combination often provides better thermal stability and antioxidant properties.
[0200] A three-layer setting of a surface layer, a middle layer, and a base layer is adopted, and each layer can be produced separately. When one of the layers is missing, only that layer needs to be produced. Compared with the overall processing method, this method can be more flexible, and the surface layer, the middle layer and the base layer can be prepared in advance, which can shorten the production time when producing PVC decorative film.
[0201] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the present invention.
Claims
1. An antibacterial PVC decorative film, characterized in that: Includes epidermis, middle layer, and basal layer; The epidermis layer comprises the following raw material components in weight ratio: 80-100 parts of PVC resin, 15-25 parts of plasticizer, and 0.05-0.1 parts of nano silver antibacterial agent; The middle layer comprises the following raw material components in weight ratio: 45-85 parts of PVC resin, 1-5 parts of heat stabilizer, 5-20 parts of titanium dioxide, 0.1-0.3 parts of 1076 antioxidant, 0.1-0.3 parts of 168 antioxidant, and 2.5-3.75 parts of antibacterial particles; The base layer comprises the following raw material components in weight ratio: 100-120 parts of PVC resin, 5-20 parts of inorganic non-metallic nano filler, 1-10 parts of coupling agent, and 20 parts of calcium carbonate powder.
2. The antibacterial PVC decorative film according to claim 1, characterized in that: The antibacterial particles include the following raw material components in weight ratio: 1.5-2 parts of nano silver particles, 0.5-0.75 parts of zinc oxide, and 0.5-1 parts of titanium dioxide; The preparation method of the nano silver particles comprises: Dissolving silver nitrate in deionized water to prepare a silver ion solution, and stirring the silver ion solution; Add a reducing agent to the silver ion solution, wait for 15-30 minutes, set the temperature at 20-35°C, and obtain an intermediate; Add a stabilizer to the intermediate, stir for 15-30 minutes, and separate by centrifugation or filtration to obtain nanosilver particles; The preparation method of the zinc oxide comprises: Dissolve zinc chloride in deionized water and set the pH range to ensure precipitation of zinc oxide; Add sodium hydroxide solution and stir to form zinc oxide precipitation; Finally, the precipitate is separated by centrifugation or filtration, washed and dried to obtain zinc oxide powder; Among them, the pH range was set to 7.8-9.2; The preparation method of titanium dioxide comprises: Dilute tetrabutyl titanate in a ratio of 1-2:10, add to deionized water, and stir evenly; The heating is performed, the temperature is set at 250-320°C, the calcination time is set to 45-75min, and finally cooling is performed to form titanium dioxide particles.
3. The antibacterial PVC decorative film according to claim 2, characterized in that: The method for preparing the antibacterial particles comprises: Mixing nanosilver particles, zinc oxide, and titanium dioxide, and stirring in deionized water; Ultrasonic treatment is performed on the mixed solution using an ultrasonic cleaner, and the treatment time is set to 15-45 minutes to obtain a mixture; The ultrasonically treated mixture was transferred to a dryer, the temperature was set at 60-80°C, and the drying time was 3-5 h; The dried mixture was pulverized and sieved using a mesh size of 100-130 μm.
4. The antibacterial PVC decorative film according to claim 3, characterized in that: The preparation method of the nano silver antibacterial agent comprises: Select PVP or PVA and dissolve them in deionized water at a ratio of 1-10% to obtain a polymer solution; Add nanosilver particles to deionized water at a ratio of 0.1-0.5%, then add the polymer solution and stir for no less than 30 minutes; Then, the mixture is treated in an ultrasonic cleaner for 15-30 minutes to form composite particles; The composite particles were then placed in a centrifuge and spun at 8000 rpm for 10-15 min to remove unbound composite particles; Add deionized water to the centrifuge tube and wash the obtained precipitate with deionized water; Finally, the composite particles are dried at a temperature of 50-60° C. to obtain the nano-silver antibacterial agent.
5. The antibacterial PVC decorative film according to claim 4, characterized in that: The inorganic non-metallic nano filler comprises the following raw material components in weight ratio: 3-10 parts of nano silicon dioxide, 2-6 parts of nano zinc oxide, 1-4 parts of nano titanium dioxide, 1-3 parts of nano zirconium oxide and 5-15 parts of nano calcium carbonate.
6. The antibacterial PVC decorative film according to claim 5, characterized in that: The preparation method of the inorganic non-metallic nanofiller comprises: Add nano silicon dioxide, nano zinc oxide, nano titanium dioxide, nano zirconium oxide, and nano calcium carbonate into a mixing container in a ratio of 3:2:1:1:5; Use a mechanical stirrer for initial mixing, and set the stirring time to 30-45 minutes; Add deionized water or ethanol to the mixing container, the added solution is 5-10% of the total amount, and continue to stir with a stirrer for 5-15 minutes; Use ultrasonic processing equipment for treatment, set the power to 100-500W, and the treatment time to 5-20min; The mixture after ultrasonic treatment is added into a vacuum dryer, the temperature is set to 40-60° C., the vacuum degree is 0.1-0.5 atm, and the drying time is 6-12 h to obtain an inorganic non-metallic nanofiller.
7. The process for preparing the antibacterial PVC decorative film according to any one of claims 1 to 6, characterized in that: The following steps are included: The base layer, the middle layer, and the epidermis layer are prepared simultaneously; Laying an intermediate layer on the base layer, bonding the intermediate layer by ultrasonic hot pressing to form a finished part, and cooling the finished part; After the workpiece is cooled, a skin layer is stacked on top, starch is applied, and then ultrasonic hot pressing is performed to form a PVC decorative film. Input the cutting size and use the automatic cutting machine to complete the cutting of the PVC decorative film.
8. The process for preparing the antibacterial PVC decorative film according to claim 7, characterized in that: During the preparation of the finished product, the ultrasonic wave is used for 5-10 seconds and the temperature is set at 70-150°C.
9. The process for preparing the antibacterial PVC decorative film according to claim 8, characterized in that: When forming the PVC decorative film, the ultrasonic wave is used for 2-6 seconds and the temperature is set to 50-120°C.
10. The process for preparing the antibacterial PVC decorative film according to claim 9, characterized in that: After the PVC decorative film is cut, the adhesion of the edge of the PVC decorative film is detected, and a threshold of the adhesion is set. When the detected value exceeds the set threshold, the PVC decorative film is determined to be qualified.
Citation Information
Patent Citations
Environment-friendly mould-proof antibacterial PVC decorative film and composite equipment thereof
CN110920189A
Preparation process and formula of antibacterial decorative film
CN111662474A
Antibacterial and mildew-proof PVC film, preparation method thereof and application of antibacterial and mildew-proof PVC film in wallpaper and furniture decorative film
CN113831663A
Antibacterial PVC decorative film and preparation method thereof
CN117402442A
